Complications of stomach ulcer with different dimensions of ulcerous defects - R. A. Abdulkhakov (Бюллетень сибирской медицины)
It was studied development of complications among 240 patients with stomach ulcer and duodenum disease with different sizes of ulcerous defects. It was discovered that among patients with big size ulcers complications occur more frequently and depend on duration of disease; bleeding is among the most frequently occurred (56.66%).